The Familiar Letter and Its Generic Boundaries - Tasevska Hadji Boshkova, Iskra (Blaze Koneski Faculty of Philology, 2020)
The aim of this paper is to investigate the nature and generic properties of familiar letter in literature overall, and more specifically in the 19th-century Macedonian literature. In the absence of more detailed accounts, I strive to analyse the character of Miladinov brothers’ epistolary, in order to re-examine the questions of factuality, fiction and the development of fictional discourse in the realm of diverse historical accounts, originating from this period. According to the immanent sociological approach of Hans Robert Jauss, which I previously explained in several of my texts on similar topic, I will try to underline the sociological dimension of familiar letter as a genre, and put it into an appropriate historical perspective. The results of this investigation should also enable a more diverse approach to this period of Macedonian literature, as well as an overview of its specific position in the world literary complex. It is expected that this analysis will also bring about questions of creativity and its specific status in the light of tradition and modernity.
Keywords: familiar letter, Miladinov brothers, fictional discourse, genre, creativity